THE CRIMINAL CASES SETTLEMENT WITH RESTORATIVE JUSTICE SYSTEM: A Case Study of Decision Number 39/Pid.Sus-Anak/2021/PNSby - Munawaroh, Siti; Firanti, Ariyanda Tri (jfpublisher, 2022)
This research aims to analize the legal regulation against children criminal act through restorative justice system. The settlement of child criminal cases against the law must be prioritized regarding the children principles and rights through the arrest, detention, and imprisonment as a ultimum remedium in a short time. This research is normative legal research since it analyze the law and regulation on children criminal act based on restorative justice, which means the solutions of the problems found in this research based on Indonesia Laws and literatures regarding the problems faced. The restorative justice is a method of resolving criminal cases that prioritizes recovery between the two parties concerned, then the retaliation does not occur in the future. Restorative Justice of Criminal Justice System in Indonesia is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, but it has not been implemented widely in its application. Since the community still needs time to adjust to applicable rules, the integrity of the facility can be fulfilled with the composition of law enforcement officials and experts who are specially trained to handle juvenile criminal cases.